Promoting siRNA delivery via enhanced cellular uptake using an arginine-decorated amphiphilic dendrimer. Issue 9 (6th October 2014) - Liu, Xiaoxuan; Liu, Cheng; Zhou, Jiehua; Chen, Chao; Qu, Fanqi; Rossi, John J.; Rocchi, Palma; Peng, Ling
Abstract : An arginine-decorated amphiphilic dendrimer is able to promote enhanced cellular uptake of siRNA, leading to considerably improved siRNA delivery and gene silencing. Abstract : RNA interference (RNAi) with small interfering RNA (siRNA) is expected to offer an attractive means to specifically and efficiently silence disease-associated genes for treating various diseases provided that safe and efficient delivery systems are available. In this study, we have established an arginine-decorated amphiphilic dendrimer composed of a hydrophobic alkyl chain and a hydrophilic PAMAM dendron bearing arginine terminals as nonviral vector for siRNA delivery. Indeed, this dendrimer proved to be very effective at delivering siRNAs in human prostate cancer PC-3 cells and in human hematopoietic CD34+ stem cells, leading to improved gene silencing compared to the corresponding nonarginine decorated dendrimer. Further investigation confirmed that this dendrimer was granted with the capacity to form stable nanoparticles with siRNA and significantly enhance cellular uptake of siRNA. In addition, this dendrimer revealed no discernible cytotoxicity. All these findings demonstrate that decoration of the dendrimer surface with arginine residues is indeed a useful strategy to improve the delivery ability of dendrimers.